2013
DOI: 10.2495/air130121
|View full text |Cite
|
Sign up to set email alerts
|

Trace element concentrations of size-fractionated particulate matter in the atmosphere of Istanbul, Turkey

Abstract: In this study, the physical characteristics and metal contents of particulate matter (PM) have been determined. In this scope, PM sampling has been done at 5 stations (Avcılar, Beşiktaş, Kilyos, Rasathane, Göztepe) for 2 years. PM filter samples were collected for 8 different size(<0.43 µm, 1-0.43 µm, 1-1.7 µm, 1.7-2.6 µm, 2.6-3.5 µm, 3.5-5 µm, 5.2-6.5 µm, 6.5-8 µm and >8 µm) using the cascade impactor. PM filters were decomposed and analyzed for 8 metals (Cr, Mn, Fe, Cu, Pb, Ni, Cd and V). According to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…Lim et al, 3 found that PM 1 and PM 2.5 had OC mass fraction as 23.0% and 22.9% while EC mass fractions was 10.4% and 9.8% respectively at ABC super Observatory at Goshan. The heavy metal fractions have also been reported higher in PM 1 in other studies worldwide 2,3,4 . However, the chemical components such as Ca and Mg which are mainly contributed by the crustal sources such as suspension of soil dust, road dust and construction dust, have lower fractions in PM 1 as compared to PM 2.5 aerosols 5,6 .…”
supporting
confidence: 51%
“…Lim et al, 3 found that PM 1 and PM 2.5 had OC mass fraction as 23.0% and 22.9% while EC mass fractions was 10.4% and 9.8% respectively at ABC super Observatory at Goshan. The heavy metal fractions have also been reported higher in PM 1 in other studies worldwide 2,3,4 . However, the chemical components such as Ca and Mg which are mainly contributed by the crustal sources such as suspension of soil dust, road dust and construction dust, have lower fractions in PM 1 as compared to PM 2.5 aerosols 5,6 .…”
supporting
confidence: 51%